2014
DOI: 10.1590/s0034-8910.2014048004711
|View full text |Cite
|
Sign up to set email alerts
|

Interface between Intellectual Disability and Mental Health: hermeneutic review

Abstract: A literature review was conducted aiming to understand the interface between the Intellectual Disability and Mental Health fields and to contribute to mitigating the path of institutionalizing individuals with intellectual deficiencies. The so-called dual diagnosis phenomenon remains underestimated in Brazil but is the object of research and specific public policy internationally. This phenomenon alerts us to the prevalence of mental health problems in those with intellectual disabilities, limiting their socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…Similar findings have been replicated in other countries across the world, e.g. Australia (Howlett, Florio, Xu, & Trollor, 2014); Brazil (Surjus & Campos, 2014) and the US (Scott & Havercamp, 2014).…”
Section: Introductionsupporting
confidence: 77%
“…Similar findings have been replicated in other countries across the world, e.g. Australia (Howlett, Florio, Xu, & Trollor, 2014); Brazil (Surjus & Campos, 2014) and the US (Scott & Havercamp, 2014).…”
Section: Introductionsupporting
confidence: 77%
“…It has been suggested that poorer living conditions of people with IDD, rather than the impairment itself, may contribute to the poor mental health in this population (Hatton, Emerson, Robertson & Baines, 2017). Abuse and having a hyperstimulating or hypostimulating environment can lead directly to psychological distress, for example (Surjus & Campos, 2014). Poverty as well as an increased likelihood of experience with the criminal justice system may also increase the probability of mental health needs (Trollor, 2014).…”
Section: Prevalence and Risk Of Adverse Mental Health In People With Iddmentioning
confidence: 99%
“…Individuals with LD were also administered measures for LD normed on its own population and is unable to correctly implement DSM-V and ICD-10 suggested methodology according to Oakland (2004) and Surjus and Campos (2014). A mixed-economy of mainly private, with some state funded, LD services exists within Brazil which means that an inconsistent, fuzzy (at best) and 'hit and miss' (at worst) assessment process exists with many people presenting with an LD never getting a diagnosis.…”
Section: Recent and Present Timesmentioning
confidence: 99%
“…The International Classification of Functioning, Disability and Health (ICFDH) (World Health Organisation, 2001), which incorporates an environmental aspect to LD, is also used in conjunction with the International Classification of Diseases (ICD-10). Brazil lacks individually administered measures for LD normed on its own population and is unable to correctly implement DSM-V and ICD-10 suggested methodology according to Oakland (2004) and Surjus and Campos (2014). A mixed-economy of mainly private, with some state funded, LD services exists within Brazil which means that an inconsistent, fuzzy (at best) and "hit and miss" (at worst) assessment process exists with many people presenting with an LD never getting a diagnosis.…”
Section: Recent and Present Timesmentioning
confidence: 99%